(untitled) (Revista "Temas Sociais", 2026)
The relationship between school, family, and community is a decisive factor for quality education, particularly in developing contexts with limited institutional resources. This qualitative case study examines the school-family-community alliance at Complexo Escolar 415 Francisco Ramos da Cruz, Sumbe, Cuanza-Sul, Angola, drawing on Epstein’s (2001) overlapping spheres model and Bronfenbrenner’s (1979) ecological systems theory. Data were collected through semi-structured interviews and focus groups with 28 purposively selected participants (4 principals, 4 teachers, 20 parents/guardians). Thematic analysis (Braun & Clarke, 2006, 2022) identified four themes: communication as the foundation of partnership, community participation as a catalyst for educational improvement, and leadership as a mediating force. Findings show a shared commitment to educational quality, yet participation remains asymmetric and largely informal. The study proposes strategic recommendations for institutionalising inclusive and participatory governance structures in Angolan primary schools.